2017
DOI: 10.1002/2017jg003859
|View full text |Cite
|
Sign up to set email alerts
|

The development of permafrost bacterial communities under submarine conditions

Abstract: Submarine permafrost is more vulnerable to thawing than permafrost on land. Besides increased heat transfer from the ocean water, the penetration of salt lowers the freezing temperature and accelerates permafrost degradation. Microbial communities in thawing permafrost are expected to be stimulated by warming, but how they develop under submarine conditions is completely unknown. We used the unique records of two submarine permafrost cores from the Laptev Sea on the East Siberian Arctic Shelf, inundated about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 87 publications
(129 reference statements)
1
24
0
Order By: Relevance
“…2a) that were retrieved along an onshore-offshore transect in the coastal region of Cape Mamontov Klyk in 2005 (Overduin, 2007;Rachold et al, 2007). Cores were named after the order of drilling and we kept this order (C1, C4, C3, C2) for better comparability with previous studies (Koch et al, 2009;Mitzscherling et al, 2017;Overduin et al, 2008;. From onshore to offshore all cores were characterized by an increase in water depth, in depth to the ice-bonded permafrost table (Fig.…”
Section: Study Site and Drillingmentioning
confidence: 85%
See 4 more Smart Citations
“…2a) that were retrieved along an onshore-offshore transect in the coastal region of Cape Mamontov Klyk in 2005 (Overduin, 2007;Rachold et al, 2007). Cores were named after the order of drilling and we kept this order (C1, C4, C3, C2) for better comparability with previous studies (Koch et al, 2009;Mitzscherling et al, 2017;Overduin et al, 2008;. From onshore to offshore all cores were characterized by an increase in water depth, in depth to the ice-bonded permafrost table (Fig.…”
Section: Study Site and Drillingmentioning
confidence: 85%
“…In a recent study, we compared submarine sediment cores from two locations on the Siberian Arctic Shelf and looked at the combined effect of permafrost inundation time and seawater intrusion on microbial communities. We showed that flooding by seawater reduced permafrost bacterial abundance and changed bacterial community composition due to the penetration of seawater into a former freshwater habitat (Mitzscherling et al, 2017). It was suggested that in addition to the effect of seawater infiltration, the sediment warming taking place over millennia could lead to proliferation.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations